Management of Tricuspid Valve Regurgitation During Surgical Ventricular Restoration for Ischemic Cardiomyopathy - Amr A. Arafat; Fatimah Alhijab; Monirah A. Albabtain; Juan Alfonso; Abdullah Alshehri; Huda Ismail; Adam I. Adam; Claudio Pragliola (Brazilian Journal of Cardiovascular Surgery, 2023)
ABSTRACT Introduction: We studied the effect of tricuspid valve (TV) surgery combined with surgical ventricular restoration (SVR) on operative outcomes, rehospitalization, recurrent tricuspid regurgitation, and survival of patients with ischemic cardiomyopathy. Additionally, surgery was compared to conservative management in patients with mild or moderate tricuspid regurgitation. To the best of our knowledge, the advantage of combining TV surgery with SVR in patients with ischemic cardiomyopathy had not been investigated before. Methods: This retrospective cohort study included 137 SVR patients who were recruited from 2009 to 2020. Patients were divided into two groups - those with no concomitant TV surgery (n=74) and those with concomitant TV repair or replacement (n=63). Results: Extracorporeal membrane oxygenation use was higher in SVR patients without TV surgery (P=0.015). Re-exploration and blood transfusion were significantly higher in those with TV surgery (P=0.048 and P=0.037, respectively). Hospital mortality occurred in eight (10.81%) patients with no TV surgery vs. five (7.94%) in the TV surgery group (P=0.771). Neither rehospitalization (log-rank P=0.749) nor survival (log-rank P=0.515) differed in patients with mild and moderate tricuspid regurgitation in both groups. Freedom from recurrent tricuspid regurgitation was non-significantly higher in mild and moderate tricuspid regurgitation patients with no TV surgery (P=0.059). Conservative management predicted the recurrence of tricuspid regurgitation. Conclusion: TV surgery concomitant with SVR could reduce the recurrence of tricuspid regurgitation; however, its effect on the clinical outcomes of rehospitalization and survival was not evident. The same effects were observed in patients with mild and moderate tricuspid regurgitation.